The art of racing in the rain a novel - Stein, Garth (New York Harper, 2008)
Nearing the end of his life, Enzo, a dog with a philosopher's soul, tries to bring together the family, pulled apart by a three year custody battle between daughter Zoe's maternal grandparents and her father Denny, a race car driver
1
Keywords: Automobile racing drivers -- Fiction; Dogs -- Fiction; Experimental fiction